Associação entre períodos de alta incidência de dengue e notificações de Leishmaniose visceral no Brasil, entre 2001e 2012 - Lucas Tadeu Silva (2016)
Health surveillance plays an important role in disease monitoring, epidemics detection, and provision of support in the planning, implementation, and evaluation of public health policies and projects. Its main source of data comes from notifications of diseases and injuries. These notifications are carried out in health information systems, with the Sistema de Informação de Agravos de Notificação (Sinan) as the main information system for surveillance in Brazil. This system has been improving since its creation in the 1990s, however, like any health information system, it has flaws. Underreporting is one of the problems in this system. Based on the hypothesis that epidemics can overload health systems and, consequently, cause underreporting of other diseases with lower impact to society, the objective was to study the association between periods of high incidence (epidemics) of dengue fever and reports of visceral leishmaniasis in Brazil, from 2001 to 2012. A retrospective, descriptive and analytical observational epidemiological study was carried out using secondary data from Sinan and the Departamento de Informática do Sistema Único de Saúde (DATASUS), considering the 26 Brazilian state capitals plus the Distrito Federal (DF) capital. Over the analyzed period and considering all 27 capitals, 1,861,533 cases of dengue fever were registered in Sinan, according to the municipality of residence, and 17,311 notifications of leishmaniasis visceral, according to the municipatility of notification. From the Sinan and DATASUSs data, the following indicators were created: dengue fevers incidence coefficient and relative notifications (notifications/100,000 inhabitants) of visceral leishmaniasis. Based on Sinans data, on the indicators created from these data and on the hypothesis addressed in this dissertation, the need to create filters to select the capital that would be analyzed was observed. According to the proposed methodology, the following capitals were selected: Boa Vista, Belém, Palmas, São Luís, Teresina, Fortaleza, Natal, João Pessoa, Recife, Maceió, Aracaju, Salvador, Belo Horizonte, Campo Grande, Cuiabá, Goiânia and Brasília. The selected group was composed of capitals located in four of the five Brazilian regions. Analyzing this group together, it was verified the presence of dengue fever seasonality with predominance of cases in the first semester and the significant predominance of visceral leishmaniasis notifications in the second half of year. For the classification of endemic and epidemic periods for dengue fever, control charts were constructed from the incidence coefficients of this disease. No reduction of visceral leishmaniasis notifications during dengue fever epidemics was observed in the cities evaluated, according to the proposed methodology. This finding may be related to the improvement of the notification process in the country, to the use of data from more developed and better-structured cities, and to the better preparedness of municipalities to deal with dengue fever epidemics due to recommendations and guidelines created specifically for these periods.